2021
DOI: 10.31729/jnma.6744
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Base Disorder in the Patients Visiting the Emergency Department of a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: An acid-base disorder is a change in the normal value of extracellular pH that may result when renal or respiratory function is abnormal or when an acid or base load overwhelms their excretory capacity. Clinical acid-base disorders are conventionally defined from the vantage point of their impact on carbonic-acid-bicarbonate buffer system. The aim of the study is to find out the prevalence of acid-base disorder among patients visiting the emergency department of a tertiary care hospital. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…During the reaction, it changes color from yellow to red; therefore, it has been used as a pH indicator in various organisms [53,55]. In individuals with respiratory disorders, the concentration of carbon dioxide increases, and the formation of carbonic acid causes respiratory acidosis, resulting in a drop in pH [25,[66][67][68]. Te results of this experiment showed that body surface redness was signifcantly reduced in group 2 compared with that in group 1 after intraperitoneal administration of phenol red in group 2, indicating respiratory acidosis due to respiratory failure caused by PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%
“…During the reaction, it changes color from yellow to red; therefore, it has been used as a pH indicator in various organisms [53,55]. In individuals with respiratory disorders, the concentration of carbon dioxide increases, and the formation of carbonic acid causes respiratory acidosis, resulting in a drop in pH [25,[66][67][68]. Te results of this experiment showed that body surface redness was signifcantly reduced in group 2 compared with that in group 1 after intraperitoneal administration of phenol red in group 2, indicating respiratory acidosis due to respiratory failure caused by PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%